Sunset Park - Auster, Paul, 1947-; Faber and Faber (London : Faber and Faber, 2010)
Four people in their twenties--including an artist, a mender of relics, a graduate student, and a man named Miles, who is a fugitive from his own family--search for hope and meaning during a time of economic crisis in the US.
Adult
Keywords: Young adults -- Fiction; Youth -- Fiction; Brooklyn (New York, N.Y.) -- Fiction; Sunset Park (New York, N.Y.) -- Fiction